(untitled) (Mustansiria Dental Journal, 2024)
This study aimed to determine and compare the shear bond strength of lingually bonded brackets via: Two—paste composite (Orthodontic Mix Bonding System), No — mix composite [Orthodontic Bonding System (No—mix)] and Light—cured composite ( Transbond XT .) Thirty extracted upper first premolars for orthodontic request were used for this investigation. The teeth were divided into three groups; each of which consisted of l0 teeth. The lingual surface of the tooth used to evaluate the lingual bond strength and the buccal surface of the same tooth utilized to evaluate the buccal bond strength. For each group of teeth investigated to determine the lingual and buccal bond shear strength, using one type of composite system for each group . The lingually bonded and buccally bonded samples were subjected to shear force using the universal compression testing machine apparatus. The lingual and buccal shear bond strengths were recorded and converted into Mpa and the data were statistically analyzed . The results showed the lingual shear bond strength insignilicantly less than that of buccal shear bond strength regarding the Orthodontic Mix Bonding System and Orthodontic Bonding System (No—mix), and the lingual shear bond strength was significantly less than the buccal shear bond strength regarding Light—cured composite (Transbond XT), The lingual and buccal shear strengths of the bonded bracket via Orthodontic Mix Bonding System were the highest than the shear bond strength of the other composite systems